Determinan Perilaku Mencari Bantuan terhadap Risiko Kesehatan Mental yang Mengarah pada Bunuh Diri di Kalangan Generasi Z di Instagram - Hadi, Ezra Aurelia Glenia; Destiwati, Rita (Jurnal The Messenger, 2025)
Purpose: This study investigated the influence of attitude (AT), subjective norms (SN), and perceived behavioral control (PBC) on help-seeking behavior using the Theory of Planned Behavior (TPB). The study also examined whether Instagram use affected the link between intention and seeking for help behavior. Instagram was chosen as the focus platform because its largest user demographic in Indonesia is Generation Z. This research addressed the urgent need to understand help-seeking patterns among Generation Z in the digital era.   Methods: A quantitative approach was applied using PLS-SEM. The sample consisted of 400 Generation Z with prior mental health concerns who actively utilized Instagram. The Slovin formula was applied to calculate the sample size at a 95% confidence level. An online questionnaire was utilized to gather the data and analyzed to assess the influence of the three TPB constructs on help-seeking intention and behavior, as well as the moderating effect of Instagram use.   Findings: AT, SN, and PBC collectively explained 87% of the variance in help-seeking behavior and 84.4% in intention. However, Instagram use did not significantly moderate the relationship between intention and behavior (p=0.321, >0.05).   Originality: This research addresses an important gap by examining how routine interaction with digital platforms may facilitate or inhibit the transition from intention to behavior. By applying the TPB framework within a socially and technologically relevant context, this study contributes both conceptually and practically to the understanding of youth mental health behavior.